Práticas avaliativas no contexto dos anos iniciais: acontecimentos, circunstâncias e significados para refletir sobre a própria prática - SANTOS, Noemia das Graças Rodrigues dos (Universidade Federal do Pará, 2018)
This research refers to my personal experience and practical evaluation developed through my work as Pedagogic Coordinator acting as Teacher’s Tutor and Assessor for students on a set of private schools. This research was conceived from memory episodes with the theme evaluation, which has been building me up as a professional. I make use, by saying such, of my own life story, seeking to analyze my path of professional development as Formation Teacher and the lived experiences on the different moments of this path. Those which are organized on eight distinct narrative episodes, each one related with all the others, hence all of them has as main theme the Diagnostic Evaluation made on the students. These episodes clarify their meaningful contributions to my acting as Students Evaluator because each one of those made it possible to come up with unique learnings, that are connected and also foresee the lived past with a view of the present that is contemplative and solidified by the nowadays theorist epistemological experiences. It helped me to understand how my professional development took place. Two moments constitute as investigational systematics where things started to take shape: 1) Important memories of themed history that occurred on my professional walk on Pedagogical Coordination; 2) How we describe those moments and how we would explain in theory its influence on our professional development? This investigation is established as a qualitative research, on the case study modality for considering that it consists on going deeper on an individual subject. It states to answer questions whether the researcher has or not control over the studied phenomena. I take as empirical material the written records of real situations, on a narrative form, occurred on my professional acting that has the theme evaluation. The analysis is structured by content analysis of the spoken reports of teachers that lived those episodes with me, producing new meanings, if compared to situations from the present date. The results of this investigation reveals researching about the very own practical shape in a reflexive matter gives us back positive results for a practical study form. The theory foundation for this research has authors that studied the evaluation on the different aspects but above all on the formation. However, I do understand that research doesn’t portrays only the moments I have lived but also on the doings that got shaped through this extended living formation.